Penerapan Pembelajaran Inovatif (PjBL & PBL) pada Materi Pemanasan Global terhadap Literasi Sains Peserta Didik Kelas X di SMA Negeri 1 Sooko Mojokerto - Anita Krisdiana; Ria Puspita; Dwikoranto (PendIPA Journal of Science Education, 2023)
This study aims to find the improvement of learning outcomes and science literacy of class X students in SMA Negeri 1 Sooko in the subject global warming through the Project Based Learning (PjBL) model in cycle I and Problem Based Learning in cycle II. The type of the research was Classroom Action Research. Based on the research that has been done, it can be concluded that the application of PBL model in cycle II can increase students’ learning outcomes and science literacy compared to the application of PjBL in cycle II. This is proven by 1) The increase of students’ average learning outcomes from 66,5 in cycle I to become 89,78 in cycle II. 2) The increase of students’ average science literacy in competency aspect from 76 in cycle I to become 88,5 in cycle II, and the increase of students’ average science literacy in attitude aspect from 50 in cycle I to become 100 in cycle II.